The Effectiveness of the TeamTeaching Method in the Islamic Religious Education Teaching - Darul Qutni; Multazam (Genius Journals, 2022)
Islamic education (PAI) is one of the obligatory General Subjects (MKU) taught at the Public Higher Education Institutions (PTU). It has broad materials, such as faith and belief, worship, morals, muamalah, siyasa, Islamic economics, and selectivity. On the other hand, it has only two credits in one semester. Due to its complex materials, perhaps the PAI lecturers may not master all of them properly. Therefore, it is necessary to use the best teaching methods to the students, such as team teaching. It is where several lecturers work together to teach parts of the material contained in one topic that has a broad scope. The results show that the team teaching method is more effective in teaching PAI at the Semarang State University (UNNES)
Keywords: PAI; PTU; team teaching